2015
DOI: 10.1103/physrevb.92.014107
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical models of hydrogen-induced defects in amorphous silicon dioxide

Abstract: We used density functional theory (DFT) calculations to model the interaction of hydrogen atoms and molecules with strained bonds and neutral oxygen vacancies in amorphous silica (a-SiO 2). The results demonstrate that the interaction of atomic hydrogen with strained Si-O bonds in defect-free a-SiO 2 networks results in the formation of two distinct defect structures, which are referred to as the [SiO 4 /H] 0 and the hydroxyl E center. To study the distribution of each defect's properties, up to 116 configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 74 publications
3
48
0
Order By: Relevance
“…The hydrogen bridge [56,116,[149][150][151][152] can be thought of as a Si − Si dimer bond decorated by a hydrogen atom. For instance, this defect may be formed by the exothermic reaction of atomic hydrogen and an oxygen vacancy [135]. Both constituents of the hydrogen bridge, namely the oxygen vacancy as well as the hydrogen atom, were experimentally found in abundance in amorphous SiO 2 : The former was experimentally confirmed by ESR studies [1,2] but also theoretically predicted in larger amounts close to the Si-SiO 2 interface as suboxides [153].…”
Section: V3 Hydrogen Bridgementioning
confidence: 82%
See 1 more Smart Citation
“…The hydrogen bridge [56,116,[149][150][151][152] can be thought of as a Si − Si dimer bond decorated by a hydrogen atom. For instance, this defect may be formed by the exothermic reaction of atomic hydrogen and an oxygen vacancy [135]. Both constituents of the hydrogen bridge, namely the oxygen vacancy as well as the hydrogen atom, were experimentally found in abundance in amorphous SiO 2 : The former was experimentally confirmed by ESR studies [1,2] but also theoretically predicted in larger amounts close to the Si-SiO 2 interface as suboxides [153].…”
Section: V3 Hydrogen Bridgementioning
confidence: 82%
“…One of them is the hydrogen bridge, which was studied in the context of gate leakage currents in transistors by Bloechl et al [7] but has not been related to charge trapping phenomena, such as drain current RTN and BTI, so far. In addition to the hydrogen bridge, a newly discovered/novel defect termed the hydroxyl E center was proposed fifteen years ago by Balk [134] and recently confirmed as a promising candidate by DFT investigations [135,136]. This defect has rarely been studied theoretically since it is not stable in crystalline SiO 2 , which is often used in DFT studies due to its well-known structure and reduced computational costs [137,138].…”
Section: Defect Candidatesmentioning
confidence: 99%
“…For example, atomic hydrogen does not react with terraces at the MgO (001) surface, but donates electrons to three-coordinated Mg sites at corners and kinks at that surface, creating new [Mg + − O-H]-type centers [35,36]. The recent study of amorphous silica has concluded that, unlike in α quartz, atomic H can break some strained Si-O bonds and form a new thermodynamically stable defect, termed hydroxyl E center [37,38]. In this case, the electron is localized on a Si atom and a proton forms an O-H bond nearby.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is recently reported that the reaction-diffusion model [11][12][13], can fail to explain the BTI degradation recovery [14][15][16][17], suggesting that charge trapping plays an important role in bias temperature instability, and more realistic microscopic model might be needed [2,[18][19][20][21][22][23]. Since charge trapping processes are usually facilitated by the defect states in the gate oxide, great efforts have been made to understand the properties of these defects as well as the intrinsic electron traping in SiO 2 and HfO 2 by using atomistic ab initio calculations [24][25][26][27][28][29][30]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…El-Sayed et al showed that the hydrogen-induced defects playing a role in amorphous SiO 2 in Ref. [26] and [27], alongside with the intrinsic electron traps in amorphous SiO 2 in Ref. [28].…”
Section: Introductionmentioning
confidence: 99%